2020
DOI: 10.1002/ptr.6802
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of medicinal herbs as a potential therapeutic option against SARS‐CoV‐2 targeting its main protease

Abstract: The COVID‐19 disease caused by the SARS‐CoV‐2 has emerged as a worldwide pandemic and caused huge damage to the lives and economy of more than hundred countries. As on May 10, 2020, more than 4,153,300 people stand infected from the virus due to an unprecedented rate of transmission and 282,700 have lost their lives because of the disease. In this context, medicinal plants may provide a way to treat the disease by targeting specific essential proteins of the virus. We screened about 51 medicinal plants and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…In consistent to this, a similar study suggested that EGCG and theaflavin mainly theaflavin-3, 3'-digallate (TF3) showed significant interaction with the receptor binding domain of SARS-CoV-2 [199]. Also, tea component Thearubigins showed strong affinity against SARS-CoV-2 3CL pro protease and it suggests that Camellia sinensis can halt replication cycle and thus, can be a potential therapeutic option against SARS-CoV-2 infection [200]. Furthermore, a study suggested that Camellia sinensis is a vital source of nutritional immunity which can increase innate immunity and mitigate the COVID-19 pandemic and disease progression [201].…”
Section: Anti-viral Potential Of Camellia Sinensissupporting
confidence: 56%
“…In consistent to this, a similar study suggested that EGCG and theaflavin mainly theaflavin-3, 3'-digallate (TF3) showed significant interaction with the receptor binding domain of SARS-CoV-2 [199]. Also, tea component Thearubigins showed strong affinity against SARS-CoV-2 3CL pro protease and it suggests that Camellia sinensis can halt replication cycle and thus, can be a potential therapeutic option against SARS-CoV-2 infection [200]. Furthermore, a study suggested that Camellia sinensis is a vital source of nutritional immunity which can increase innate immunity and mitigate the COVID-19 pandemic and disease progression [201].…”
Section: Anti-viral Potential Of Camellia Sinensissupporting
confidence: 56%
“…A summary of the pathways involved in EGCG mode of action can be found in Xu et al (2017) [12]. Green tea extracts have been proposed before by in silico modelling and in in vitro assays as inhibitors of the SARS-CoV-2 chymotrypsin-like protease [46,47]. However, the IC 50 values for EGCG mediated inhibition were lower for virus compared to pseudotyped vectors, which suggests that a dominate effect of EGCG on SARS-CoV-2 protease is not very likely.…”
Section: Discussionmentioning
confidence: 99%
“…3-Chymotrypsin-like protease is necessary for viral replication and as such an important drug target for SARS-CoV-2 therapeutic agents. Other 3chymotrypsin-like cysteine protease Upadhyay et al, 2020;ul Qamar et al, 2020;Benarba and Pandiella, 2020) potential mechanisms through which medicinal plants act which are also important targets for therapeutic agents include angiotensin-converting enzyme 2 (ACE2) (Table 3), SARS-CoV-PLpro activity (Table 4), SARS-CoV helicase (Table 5), Type II Transmembrane Serine Protease (TMPRSS2) (Table 6), RNA-dependent RNA p o l y m e r a s e ( R d R p ) ( T a b l e 7 ) a n d Immunomodulatory activities (Table 8). Wen et al, 2011;Choi et al, 2004;Lim et al, 2019…”
Section: Potential Mechanism Of Action Of Plants Used Against Sars-cov-2mentioning
confidence: 99%